Analysis of DC MCB Usage Characteristics for AC and DC Load Usage - Sarwan Hamid; Jamaaluddin Jamaaluddin; Dwi Hadidjaja Rasjid Saputra; Arief Wisaksono (Procedia of Engineering and Life Science, 2022)
One of the most important and expensive power lines in the distribution method is the low line voltage. In case of overload or short circuit current, it protects the electrical installation. MCB is an important component in electrical installations. The formation of sparks due to a short circuit can eventually cause a fire which has the potential to cause a fire, which is an unwanted MCB nuisance. This MCB can be used as a direct current breaker with a load, either manually or automatically. When the MCB is switched from "ON" to "OFF", the mechanical part in the MCB cuts off the electric current. The manual method involves turning off the toggle switch in front of the MCB (usually blue or black). The finished tool is then tested to see how well components such as AC MCB, DC MCB, Volt meter, LED lamps, Outlets, and lamp fittings perform. The function of the analysis of the characteristics of the use of DC MCBs for the use of DC loads works to compare the use of DC MCBs on AC loads and which ones are the most effective and the circuit is given a load until the MCB trips and amperes and volts are measured in the circuit.